2017
DOI: 10.1186/s12884-017-1617-9
|View full text |Cite
|
Sign up to set email alerts
|

Is unplanned out-of-hospital birth managed by paramedics ‘infrequent’, ‘normal’ and ‘uncomplicated’?

Abstract: BackgroundUnplanned out-of-hospital birth is often perceived as precipitate in nature, ‘infrequent’, ‘normal’ and ‘uncomplicated’. However, international studies report unplanned out-of-hospital birth is associated with increased rates of maternal and neonatal morbidity and mortality. This research describes intrapartum, immediate postpartum and neonatal care provided by paramedics in Queensland, Australia. The objectives were to (1) determine the number of cases where the paramedic documented birth or imminen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
29
0
17

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 38 publications
(35 reference statements)
5
29
0
17
Order By: Relevance
“…As described by us and McLelland et al [23], most of the births (79%) occurred between the hours of 20.00 and 08.00 [24]. Moreover, Flanagan et al reported in a retrospective analysis of 192 unplanned out-of-hospital births, that 21% of the newborns had an Apgar score scored ≤7 out of 10, whereas in our cohort, it represented only 14% of the newborns [25]. Contrary to previous reports, a considerable proportions of mothers in our cohort (23.6%) had a midwife consultation in the 24 previous hours.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…As described by us and McLelland et al [23], most of the births (79%) occurred between the hours of 20.00 and 08.00 [24]. Moreover, Flanagan et al reported in a retrospective analysis of 192 unplanned out-of-hospital births, that 21% of the newborns had an Apgar score scored ≤7 out of 10, whereas in our cohort, it represented only 14% of the newborns [25]. Contrary to previous reports, a considerable proportions of mothers in our cohort (23.6%) had a midwife consultation in the 24 previous hours.…”
Section: Discussionsupporting
confidence: 56%
“…Contrary to previous reports, a considerable proportions of mothers in our cohort (23.6%) had a midwife consultation in the 24 previous hours. For instance, Flanagan et al reported that only 2.4% ( n = 15) of women who birthed before arrival stated that they had been sent home from hospital within the 12 previous hours [25].…”
Section: Discussionmentioning
confidence: 99%
“…One Swedish study supports the low frequency of debrief sessions after stressful events in out‐of‐hospital care (Bohström et al, ), as well as describes how collegial support and discussions with colleagues can be a positive strategy for stress reducing after stressful events such as childbirth. The increased risk of infant morbidity and mortality, compared with births in obstetric institutions, is well documented (Engjom et al, ; Flanagan et al, ; Jones et al, ; Nguyen et al, ), even though one study from Finland reports no major perinatal or maternal cases in their sample (Pirneskoski, Peräjoki, Nuutila, & Kuisma, ). Maternal outcomes, such as postpartum haemorrhage and severe perineal tears, are however not fully understood (Ford & Pett, ; Unterscheider et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Unplanned out‐of‐hospital births are associated with an increased risk of infant mortality compared with births in obstetric institutions (Engjom et al, ; Jones et al, ; Nguyen, Lefevre, & Dreyfus, ). One Australian study reported that 11% of women attended by EMTs during labour gave birth before arriving at hospital; of these, 27% were recorded with antenatal and/or intrapartum complications, while 22% of the babies were recorded with an Apgar score lower than 7 (Flanagan, Lord, & Barnes, ). Risk factors associated with both maternal and neonatal outcomes in unplanned out‐of‐hospital births include maternal characteristics (young maternal age, low socio‐economic status, immigrant background, smoking), pregnancy‐related factors (multiparity, placental conditions, low birthweight, prematurity, infections, concealed pregnancy) and poor antenatal care (Boland et al, ; Engjom, Morken, Høydahl, Norheim, & Klungsøyr, ; Gunnarsson, Fasting, Skogvoll, Smárason, & Salvesen, ; Jones et al, ; Nguyen et al, ; Unterscheider et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Although childbirth care in health facilities or accompanied by skilled health personnel is encouraged, in various regions of the world, especially in low-income countries, home births represent more than 50% of the total number of births [ 9 , 10 ]. Higher rates of maternal and perinatal complications and deaths have been described in home births, as well as difficulties in managing complications due to the need for transfer to a health facility [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%